CSR Disclosure and Firm Value: Is Customer Loyalty Matter? - Sitepu, Immanuel Alessandro; Sriani, Dewi (Accounting Research Unit (ARU Journal), 2024)
This study aims to investigate the effect of Corporate Social Responsibility (CSR) Disclosure on firm value through mediation of customer loyalty. This study used manufacturing public companies listed in the Indonesian Stock Exchange during 2018-2022. The final sample is 109 firm year observations based on purposive sampling. This study uses quantitative approach and analyze secondary data obtained from OSIRIS Dataset and sustainability reports. The data are examined using path analysis and bootstrapping method in Model 4 PROCESS Macro for SPSS 25 by Andrew Hayes. .The results show that CSR Disclosure doesn’t affect customer loyalty and firm value. Customer loyalty doesn’t affect firm value as well. In addition, customer loyalty does not mediate the relationship between CSR disclosure and firm value. The novelty of this study is using content analysis in measuring CSR Disclosure with the extended measurement and the use of public market share as measurement of customer loyalty in public manufacturing companies.